The Effect Of Using Different Feedback Timings To Schedule Consistence And Varied Practice According To The Mastery Learning Style To Learn Vaulting Horse Skills For 3rd Grade Pupils - Kadhim, Abedulrazaaq (Journal of Physical Education, 2016)
The importance of the research lies in using different timings for feedback to schedule consistent and varied practice according to mastery of learning style to learn jumping on the vault in gymnastics by pupils. The problem of the research lies in the pupils’ weakness in performing gymnastic skills specially vaulting on the vault during physical education class. The researcher used the experimental method. The subjects were (28) third year pupils from Al Tekamul elementary school/ Baghdad of the academic year 2015 – 2016 all aged nine years old